Vildagliptin Attenuates Myocardial Dysfunction and Restores Autophagy via miR-21/SPRY1/ERK in Diabetic Mice Heart - Li, Xiaochen; Meng, Cheng; Han, Fei; Yang, Juhong; Wang, Jingyu; Zhu, Yanjuan; Cui, Xiao; Zuo, Minxia; Xu, Jie; Chang, Baocheng (Frontiers in Pharmacology, 2021)
AIM: Vildagliptin (vild) improves diastolic dysfunction and is associated with a lower relative risk of major adverse cardiovascular events (MACE) in younger patients. The present study aimed to evaluate whether vild prevents the development of diabetic cardiomyopathy in type 2 diabetic mice and identify its underlying mechanisms. METHODS: Type 2 diabetic mouse model was generated using wild-type (WT) (C57BL/6J) and miR-21 knockout mice by treatment with HFD/STZ. Cardiomyocyte-specific miR-21 overexpression was achieved using adeno-associated virus 9. Echocardiography was used to evaluate cardiac function in mice. Morphology, autophagy, and proteins levels in related pathway were analyzed. qRT-PCR was used to detect miR-21. Rat cardiac myoblast cell line (H9c2) cells were transfected with miR-21 mimics and inhibitor to explore the related mechanisms of miR-21 in diabetic cardiomyopathy (DCM). RESULTS: Vild restored autophagy and alleviated fibrosis, thereby enhancing cardiac function in DM mice. In addition, miR-21 levels were increased under high glucose conditions. miR-21 knockout DM mice with miR-21 knockout had reduced cardiac hypertrophy and cardiac dysfunction compared to WT DM mice. Overexpression of miR-21 aggravated fibrosis, reduced autophagy, and attenuated the protective effect of vild on cardiac function. In high-glucose-treated H9c2 cells, the downstream effectors of sprouty homolog 1 (SPRY1) including extracellular signal-regulated kinases (ERK) and mammalian target of rapamycin (mTOR) showed significant changes following transfection with miR-21 mimics or inhibitor. CONCLUSIONS: The results of our study indicate that vild prevents DCM by restoring autophagy through the miR-21/SPRY1/ERK/mTOR pathway. Therefore, miR-21 is a target in the development of DCM, and vild demonstrates significant potential for clinical application in prevention of DCM.